The Trypanosoma cruzi Protein TcHTE Is Critical for Heme Uptake. - Marcelo L Merli; Lucas Pagura; Josefina Hernández; María Julia Barisón; Elizabeth M F Pral; Ariel M Silber; Julia A Cricco (Public Library of Science (PLoS), 2016)
Trypanosoma cruzi, the etiological agent of Chagas' disease, presents nutritional requirements for several metabolites. It requires heme for the biosynthesis of several heme-proteins involved in essential metabolic pathways like mitochondrial cytochromes and respiratory complexes, as well as enzymes involved in the biosynthesis of sterols and unsaturated fatty acids. However, this parasite lacks a complete route for its synthesis. In view of these facts, T. cruzi has to incorporate heme from the environment during its life cycle. In other words, their hosts must supply the heme for heme-protein synthesis. Although the acquisition of heme is a fundamental issue for the parasite's replication and survival, how this cofactor is imported and distributed is poorly understood. In this work, we used different fluorescent heme analogs to explore heme uptake along the different life-cycle stages of T. cruzi, showing that this parasite imports it during its replicative stages: the epimastigote in the insect vector and the intracellular amastigote in the mammalian host. Also, we identified and characterized a T. cruzi protein (TcHTE) with 55% of sequence similarity to LHR1 (protein involved in L. amazonensis heme transport), which is located in the flagellar pocket, where the transport of nutrients proceeds in trypanosomatids. We postulate TcHTE as a protein involved in improving the efficiency of the heme uptake or trafficking in T. cruzi.